An objective method of validating pure-tone threshold - Raghunath M (Journal of All India Institute of Speech and Hearing, 1970)
Because of the serious limitation of the pure-tone audiometry, more and more objective techniques are sought to arrive at accurate and valid thresholds. The present study is th~reforean attempt to compute hearing thresholds from the stapedial reflex thresholds